2016
DOI: 10.3892/ol.2016.4832
|View full text |Cite
|
Sign up to set email alerts
|

ATF3 suppresses ESCC via downregulation of ID1

Abstract: Esophageal cancer is one of the most prevalent forms of cancer and has a particularly high mortality rate due to early metastasis; however, the underlying mechanisms of its formation and progression remain unclear. The present study performed immunohistochemical analysis and observed that the expression of activating transcription factor 3 (ATF3) was reduced in esophageal squamous cell carcinoma (ESCC) in comparison with non-tumor adjacent tissues. By contrast, inhibitor of DNA binding 1 (ID1) was overexpresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…These ndings were supported by analysis of data in public databases, including TCGA and GEO. Furthermore, consistent with our results, IFI6 overexpression is implicated in multiple malignant diseases [22,44,45], and the increase in ATF3 expression was associated with a favorable prognosis in patients with ESCC [46,47].…”
Section: Discussionsupporting
confidence: 91%
“…These ndings were supported by analysis of data in public databases, including TCGA and GEO. Furthermore, consistent with our results, IFI6 overexpression is implicated in multiple malignant diseases [22,44,45], and the increase in ATF3 expression was associated with a favorable prognosis in patients with ESCC [46,47].…”
Section: Discussionsupporting
confidence: 91%
“…ATF3 is a well-characterized, known repressor of ID1 expression. 24 It will be interesting to determine if UBR5 destabilizes ATF3. It is equally possible that loss of UBR5 leads indirectly to the loss of a positively acting transcription factor that controls ID1/ID3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…ATF3 may play different roles in various tumors. Li et al [ 28 ] found that ATF3 was reduced in esophageal squamous cell carcinoma (ESCC) compared with non-tumor adjacent tissues and ATF3 suppressed ESCC via downregulation of ID1. In bladder cancer, ATF3 suppresses metastasis of bladder cancer by regulating gelsolin-mediated remodeling of the actin cytoskeleton [ 11 ].…”
Section: Discussionmentioning
confidence: 99%